The specific impact of social media communications on the role of clans in the culture of Iraqi society - Marzoog, Othman Mohammed (Journal of the Belarusian State University. Journalism, 2023)
This article presents the analytical results of the social media communications impact on the role of single lineage groups (clans) in the culture of Iraqi society. Taking into account the gender, age and education of the respondents, the article analyses their answers to the questions about their attitudes towards the social media publications about the role of clan in the modern life of Iraq.
Keywords: culture; social communication; clan; tribal solidarity; social media; users